Usability of Mobile Applications: A Systematic Literature Study - Weichbroth, Pawel (IEEE access, 2020)
Since the release of the first mobile devices, the usability of on-board applications has been the concern not only of software vendors but hardware manufacturers as well. The academia community later willingly joined the discussion on usability in terms of theory and empirical measurement, having experience and knowledge in desktop settings. At first sight, such a background should guarantee a solid foundation to conduct research on software usability in a new setting. However, a preliminary study on the subject matter revealed methodological disorder in contemporary literature. As a matter of fact, a need emerged to review existing usability definitions, attributes and measures to recognize all associated aspects. In order to fill this void, we conducted a systematic literature review on usability studies indexed by the Scopus database and devoted to mobile applications. The input volume covers 790 documents from 2001 to 2018. The data analysis shows that the ISO 9241-11 usability definition has been adopted in an unchanged form and popularized as the standard by the HCI community. Secondly, in total, 75 attributes were identified and analysed. The most frequent are efficiency (70%), satisfaction (66%) and effectiveness (58%), which directly originate from the above definition. Subsequently, the less frequent are learnability (45%), memorability (23%), cognitive load (19%) and errors (17%). The last two concern simplicity (13%) and ease of use (9%). Thirdly, in the evaluation of usability, controlled observation and surveys are two major research methods applied, while eye-tracking, thinking aloud and interview are hardly used and serve as complementary to collect additional data. Moreover, usability evaluations are often confused with user experience dimensions, covering not only application quality characteristics, but also user beliefs, emotions and preferences. All these results indicate the need for further research on the usability of mobile applications, aiming to establish a consensus in the theory and practice among all interested parties.